Syurga di Telapak Kaki Ibu (Melayu Nusantara) - Wisnu Zikrul Liandi; Uswatul Hakim (Misterius: Publikasi Ilmu Seni dan Desain Komunikasi Visual, 2025)
The musical work “Syurga di Telapak Kaki Ibu” is a rearrangement of the Malay song composed by S. Effendi in 1990 and popularized by Aishah. This work highlights moral and religious values about honoring mothers. The purpose of this study is to describe the creative process of rearranging “Syurga di Telapak Kaki Ibu” using the rentak langgam format characteristic of Malay music. A descriptive–qualitative approach with a work-study method was employed. Data were collected through observation, literature review, and the composer’s five-month practice. The results show a new arrangement featuring a mournful melody, flowing harmonies, and the application of ornamentation techniques such as cengkok and grenek on melodic instruments (gambus oud, sape, bamboo flute, violin, accordion). The arrangement is structured in intro, verse, interlude, verse, interlude, and coda to create more varied emotional nuances while preserving the original essence of the song. This work is expected to strengthen the existence of classic Malay songs in the era of modern music and serve as a reference for students and traditional music practitioners in creating innovative works based on cultural heritage.